AB1203-HPR Comparison of quality of life of patients with rheumatoid arthritis, psoriatic arthritis and ankilosing spondilitis with treatment or prescription of biologic drugs: results from the cara study. (15th June 2017) - Sinigaglia, L; Scalone, L; Sarzi-Puttini, P; Montecucco, CM; Giacomelli, R; Lapadula, G; Olivieri, I; Giardino, A; Didoni, G; Cortesi, P; Mantovani, LG; Mecchia, M; et al.
Abstract : Background: Chronic rheumatic conditions such as rheumatoid arthritis (RA), ankylosing spondylitis (AS), and psoriatic arthritis (PsA) are associated with severe morbidity and significant impairment of patients' health related quality of life (HRQoL). Several treatments are available but not all the patients respond positively to them. Biologic therapies such as anti-TNFα agents are shown to benefit who fail or have partial responses to standard DMARD therapy. Objectives: Within a multicenter stated preferences study (CARA Study), we assessed HRQoL in patients with RA, AS and PsA, and estimated relationship of HRQOL with the different diagnoses, clinical characteristics and biological treatment experience. Methods: Patients with RA, AS, or PsA, who at the time of enrollment were following a treatment (experienced) or received a first prescription (naïve) of treatment with biological drugs were enrolled. Together with preferences data, clinical and HRQOL information was reported. HRQoL was assessed with the recently developed and successfully validated version of the EQ-5D-5L, which allows to obtain a description of health (in 5 domains and 5 levels of severity each), a measure (EQ-VAS) and a valuation (utility) of health. Multiple linear regression analyses were conducted to assess the association between EQ-5D VAS score and the utility with age, sex, diagnosis, treatment experience, years from symptoms onset and years from diagnosis. Results: 513 patients were enrolled (mean±SD =50.0±13.6, 42.5% female). As regards the diagnosis, 33.9% had RA, 34.9% PsA and 31.2% AS. The mean±SD time from the symptoms onset was 10.8±9.4 and from the diagnosis was 8.0±8.2 years. Almost half of the patients (47.4%) were naïve to the biological treatment. Patients reporting severe or extreme problems were: 7.1% in mobility, 3.6% in self-care, 10.3% in usual activities, 18.6% in pain/discomfort, 5.5% in anxiety/depression. The mean±SD of the VAS was 60.4±20.5 and of the utility was 0.773±0.116. From the regression model the VAS and utility are significantly (p<0.05) associated with age, sex and treatment experience (table 1 ). In particular, the patients being naïve to the treatment with biological drugs had on average significant worse levels of HRQoL than experienced patients, adjusting for the other variables included in the model. Conclusions: Patients naïve to biological treatment have significat lower levels of HRQoL, suggesting that their current situation is not satisfactory and need to start with a more effective treatment. Disclosure of Interest: L. Sinigaglia: None declared, L. Scalone: None declared, P. Sarzi-Puttini: None declared, C. Montecucco: None declared, R. Giacomelli Grant/research support from: MSD, G. Lapadula: None declared, I. Olivieri: None declared, A. Giardino Employee of: MSD Italia, G. Didoni Employee of: MSD Italia, P. Cortesi Grant/research support from: Gilead, L. Mantovani: None declared, M. Mecchia Employee of: MSD Italia